2011
DOI: 10.1117/1.3659200
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thermal effects of interstitial laser phototherapy on mammary tumors using proton resonance frequency method

Abstract: Abstract. Laser immunotherapy (LIT) uses a synergistic approach to treat cancer systemically through local laser irradiation and immunological stimulation. Currently, LIT utilizes dye-assisted noninvasive laser irradiation to achieve selective photothermal interaction. However, LIT faces difficulties treating deeper tumors or tumors with heavily pigmented overlying skin. To circumvent these barriers, we use interstitial laser irradiation to induce the desired photothermal effects. The purpose of this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…The temperature mapping results showed that the selective laser photothermal effect could increase tumor temperatures in a range of 10 to 25°C [83]. In a study by Le et al, different power settings (1.0, 1.25, and 1.5 W) were applied for 10 min in a rat tumor, demonstrating an increase in temperature that ranged from 8°C to 15°C based on different laser power and distance from the injected optical fiber [84]. …”
Section: Mechanism Of Incvaxmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature mapping results showed that the selective laser photothermal effect could increase tumor temperatures in a range of 10 to 25°C [83]. In a study by Le et al, different power settings (1.0, 1.25, and 1.5 W) were applied for 10 min in a rat tumor, demonstrating an increase in temperature that ranged from 8°C to 15°C based on different laser power and distance from the injected optical fiber [84]. …”
Section: Mechanism Of Incvaxmentioning
confidence: 99%
“…Reproduced with permission from [84]. Copyright 2011 Society of Photo Optical Instrumentation Engineers.…”
Section: Figurementioning
confidence: 99%
“…LIT employs an in situ light absorbing dye to selectively enhance photothermal effect. Accurate determination of target tissue temperature is essential in understanding and optimizing the photothermal effect of LIT [7][8].…”
mentioning
confidence: 99%
“…And temperature measurement based on water proton resonance frequency (PRF) in MRT has been used for interstitial laser therapy. 15,16 MRT provided noninvasive three-dimensional temperature distribution with high sensitivity. However, it had relatively low temporal resolution and its cost and complexity severely limited its practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Current noninvasive methods to measure tissue temperature include infrared thermography, [11][12][13] ultrasound thermograph, 14 and magnetic resonance thermometry (MRT). [15][16][17] Infrared thermography could provide sensitive and real-time detection. However, it can only measure surface temperature.…”
Section: Introductionmentioning
confidence: 99%